In senescence, age‐associated B cells secrete TNFα and inhibit survival of B‐cell precursors*. Issue 2 (17th March 2013) - Ratliff, Michelle; Alter, Sarah; Frasca, Daniela; Blomberg, Bonnie B.; Riley, Richard L.
Summary Aged mice exhibit ~ 5–10‐fold increases in an ordinarily minor CD21/35− CD23− mature B‐cell subset termed age‐associated B cells (ABCs). ABCs from old, but not young, mice induce apoptosis in pro‐B cells directly through secretion of TNFα. In addition, aged ABCs, via TNFα, stimulate bone marrow cells to suppress pro‐B‐cell growth. ABC effects can be prevented by the anti‐inflammatory cytokine IL‐10. Notably, CD21/35+ CD23+ follicular (FO) splenic and FO‐like recirculating bone marrow B cells in both young and aged mice contain a subpopulation that produces IL‐10. Unlike young adult FO B cells, old FO B cells also produce TNFα; however, secretion of IL‐10 within this B‐cell population ameliorates the TNFα‐mediated effects on B‐cell precursors. Loss of B‐cell precursors in the bone marrow of old mice in vivo was significantly associated with increased ABC relative to recirculating FO‐like B cells. Adoptive transfer of aged ABC into RAG‐2 KO recipients resulted in significant losses of pro‐B cells within the bone marrow. These results suggest that alterations in B‐cell composition during old age, in particular, the increase in ABC within the B‐cell compartments, contribute to a pro‐inflammatory environment within the bone marrow. This provides a mechanism of inappropriate B‐cell 'feedback' that promotes down‐regulation of B lymphopoiesis in old age.